Bioenergy and agriculture: Promises and challenges: Developing bioenergy: A win-win approach that can serve the poor and the environment - Hazell, Peter B. R. (International Food Policy Research Institute, 2006)
The promise of bioenergy is that it may help cope with rising energy prices, address environmental concerns about greenhouse gas emissions, and offer new income and employment to farmers and rural areas. In principle, there is a high degree of congruency between these three objectives for bioenergy production and the poverty reduction targets embodied in the Millennium Development Goals. But the development of bioenergy also poses risks and has the potential to result in difficult trade-offs for the poor and the environment. There is, for example, a chicken-and-egg conundrum that makes it difficult for the private sector to grow the industry before sufficient demand is forthcoming, yet demand depends on an ample and well distributed supply. Moreover, because most of the environmental and social benefits and costs of bioenergy are not priced in the market, leaving bioenergy development entirely to the private sector and the market will lead to levels and types of bioenergy production that fail to achieve the best environmental and social outcomes. To ensure better outcomes, the public sector has important roles to play.